The ghost ship mystery - Warner, Gertrude Chandler, 1890-1979. (New York, N.Y. : Scholastic, 1994)
While visiting the seaport town of Ragged Cove, Massachusetts, the Alden children find the ship's log of the Flying Cloud, shipwrecked in 1869, supposedly during a mutiny.
Keywords: Shipwrecks -- Fiction